Modelos cosmológicos quânticos com fluido perfeito - Fracalossi, Raphael (2018)
In this work, quantum cosmological models with perfect fluid are studied according to the canonical approach of Quantum Cosmology. The material content of the Universe is described by Schutz’s formalism, which is discussed in detail and used as a tool in order to solve the problem of absence of a time variable in theory. In this context, two models are constructed containing a stiff matter fluid. In the first one, a two-fluid model, stiff matter and radiation in a homogeneous and isotropic Universe described by FLRW metric. It is observed that the initial singularity in the classic model is apparently removed in the quantum approach. In the second, an anisotropic quantum cosmological model described by Kantowski-Sachs metric is discussed. As a result, it is found that although the Hamiltonian operator associated with the model is symmetric, the norm of wave function of Universe is time-dependent, implying loss of unitarity, reinforcing the existence of a pathology already verified in quantum cosmological model described by Bianchi I anisotropic metric.